Attachment beyond the mother: Investigating the paternal role in building adolescents’ adversity quotient in urban Indonesian high schools - Aisyah Pramudita; Melly Latifah; Yulina Eva Riany (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2025)
The dynamics of adolescent today were considered not to have reached the stage of formal operational cognitive development where adolescent should have been able to analyze problem solving and be able to find alternative solution to their problem, this dynamic is suspected because adolescent have an inability to deal with problem/difficulty, which cause them not to be tough enough and experience mental health issue. This research provides novelty as it analyze how the father's role in the building adolescent adversity quotient, where attachment is usually identified with maternal attachment. This study aims to investigating paternal attachment on building adolescent’s adversity quotient. This study used a quantitative approach with an explanatory method, as many as 398 high school student in Bogor City were sampled used random sampling, 398 respondent from 4 different high school were taken as sample (2 SMAN and 2 SMAS). Instrument used in this study are translated instrument into bahasa, 1) IPPA-R which has been revised by Gullone and Robinson (2005) with 28 item question and Cronbach's alpha of 0.882; 2) Adversity Quotient which has been adapted by Wang et al. (2022) with 24 item question and Cronbach's alpha of 0.682. The data obtained went through statistical testing used SPSS to obtain correlation, regression and comparison. The result revealed that adolescent characteristic, family characteristic and paternal attachment simultaneously have a significant effect of 8.0 percent on adversity quotient. This research can serve as a base for the development of paternal attachment and adolescent adversity improvement program in the community (family, school and government).